PELATIHAN PEMBUATAN SABUN CAIR KEPADA IBU-IBU BADAN KESWADAYAAN (BKM) DAMAI SEJAHTERA KELURAHAN SUKARAJA KECAMATAN MEDAN MAIMUN - Jeudi Agustina Taman Parulian Sianturi; Anton A. P. Sinaga; Henri Saragih; Elperida J. Sinurat; Maludin Panjaitan; Jon Henri Purba; Hotlan Butar-Butar; Junika Napitupulu; Kristanty M. N. Nadapdap; Mangasa Panjaitan; Jansen Hutabarat (Universitas Methodist Indonesia, 2022)
Increasing people's income can be done with various approaches, by conducting training for the community. Conducting training for mothers who are members of the Peaceful Prosperous Self-help Agency (BKM) in Sukaraja Village – Medan Maimun District. Through training in making liquid soap, it is hoped that it will increase human resources who are able to rely on their own strength. The purpose of this training is to make your own liquid laundry soap and motivate mothers so they can increase their income. The results obtained were that the enthusiasm of the participants was extraordinary and hoped that the training activities would continue to be carried out.